Lymphomatoid granulomatosis involving the central nervous system: A case report and review of the literature - LIU, HONGLI (D.A. Spandidos, 2014)
Lymphomatoid granulomatosis (LYG) is a rare tumor with unknown etiology. Specific etiological factors for LYG are also unknown, although previous data indicates that LYG is an Epstein-Barr virus-associated B-cell proliferation associated with an exuberant T-cell reaction. According to the 2008 WHO classification, LYG is characterized by B-cell proliferation of B-lymphoma cells. Generally, treatment options for LYG are similar to those for diffuse large B-cell lymphoma. Unfortunately, LYG is a chemotherapy-resistant disease in certain patients and has a poor prognosis. The current study presents the case of a 19-year-old male patient with pulmonary LYG. The patient exhibited progressive disease following one cycle of chemotherapy with cyclophosphamide, adriamycin, vincristine and prednisone, and nodular lesions in the brain were diagnosed. Radiotherapy was delivered to the whole brain, however, this treatment did not prevent progression of the disease and the patient succumbed three months after initial presentation. An overview of the literature with regard to the etiology, clinical features, diagnosis and treatment options for LYG is also presented in the current case study.